Convergent antibody responses are associated with broad neutralization of hepatitis C virus - Skinner, Nicole E.; Ogega, Clinton O.; Frumento, Nicole; Clark, Kaitlyn E.; Paul, Harry; Yegnasubramanian, Srinivasan; Schuebel, Kornel; Meyers, Jennifer; Gupta, Anuj; Wheelan, Sarah; Cox, Andrea L.; Crowe, James E.; et al. (Frontiers in Immunology, 2023)
Early development of broadly neutralizing antibodies (bNAbs) targeting the hepatitis C virus (HCV) envelope glycoprotein E2 is associated with spontaneous clearance of infection, so induction of bNAbs is a major goal of HCV vaccine development. However, the molecular antibody features important for broad neutralization are not known. To identify B cell repertoire features associated with broad neutralization, we performed RNA sequencing of the B cell receptors (BCRs) of HCV E2-reactive B cells of HCV-infected individuals with either high or low plasma neutralizing breadth. We found distinctive BCR features associated with broad neutralization of HCV, including long heavy chain complementarity determining region 3 (CDRH3) regions, specific VH gene usage, increased frequencies of somatic hypermutation, and particular VH gene mutations. Most intriguing, we identified many E2-reactive public BCR clonotypes (heavy and light chain clones with the same V and J-genes and identical CDR3 sequences) present only in subjects who produced highly neutralizing plasma. The majority of these public clonotypes were shared by two subjects who cleared infection. We produced a monoclonal antibody (mAb) expressed by pairing the most abundant public heavy and light chains from these clearance, high neutralization public clonotypes. This mAb had features enriched in high neutralization clonotypes, such as increased somatic hypermutation frequency and usage of IGHV1-69, and was cross-neutralizing. Together, these results demonstrate distinct BCR repertoires associated with high plasma neutralizing capacity. Further characterization of the molecular features and function of these antibodies can inform HCV vaccine development.